PERAN MASYARAKAT DALAM PERENCANAAN DAN PENGELOLAAN PEMBANGUNAN STUDI KASUS DI DESA DURIA, KECAMATAN LOLOFITUMOI KABUPATEN NIAS BARAT - Adil Berkatman Jaya Gulo; Jonson Rajagukguk; Vera Pasaribu; Maringan Panjaitan (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This study analyzes the role of the community in the planning and management of development in Duria Village, Lolofitu Moi Subdistrict, West Nias Regency, aiming to understand how residents’ participation affects the effectiveness of village development. A descriptive qualitative method was employed, with data collected through in-depth interviews and official documentation. The findings reveal that the community actively participates in village meetings and program priority-setting, although some residents still rely on traditional leaders or representatives. In management, participation is evident through collective work (gotong royong), utilization of development outcomes, budget oversight, and women’s involvement in non-physical programs such as the Family Welfare Movement (PKK). Supporting factors include a culture of mutual cooperation, open leadership, and direct benefits, while major obstacles are low education, dominance of certain figures, vulnerable economic conditions, and limited village budgets. In conclusion, community participation is relatively effective but requires expansion and quality improvement, especially for vulnerable groups. These findings provide insights for village governments to achieve participatory, transparent, and sustainable development.